Hubungan Kekuatan Otot Lengan Dan Panjang Lengan Dengan Hasil Servis Atas Pada Permainan Bola Voli Siswa SMK Negeri 6 Tidore Kepulauan - Triana Nuryastuti; Isnardi Ismail (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to obtain a clear picture of the relationship between arm muscle strength and arm length with service results for students at SMK Negeri 6 Tidore Islands. The benefits in this research are physical education teachers, coaches and athletes for the development of volleyball learning, especially about the top serve technique and it is hoped that it will be able to help students to improve their ability to serve in volleyball games in order to achieve better performance. This research was conducted on class XI students of SMK Negeri 6 Tidore Islands in May 2022. The sample used was 20 students of class XI. Data analysis used normality test to test the normality of the data. Furthermore, a simple correlation analysis test was conducted to determine the relationship between variables and followed by a t-test to determine the level of significance. The results of the simple correlation test analysis show that the results of rcount = 0.843 > from rtable = 0.361 which means that there is a relationship between variables, then proceed with the t test where tcount = 5.39 > from ttable = 1.697 which means there is a significant relationship between variables. So it can be concluded that there is a significant relationship between arm muscle strength and arm length with service results for students at SMK Negeri 6 Tidore Islands